2007
DOI: 10.1111/j.1472-4658.2007.05816.x
|View full text |Cite
|
Sign up to set email alerts
|

Seven‐up facilitates insect counter‐defense by suppressing cathepsin B expression

Abstract: Herbivorous insects are constantly challenged by a broad spectrum of toxins and antinutritional factors produced by their host plants. The insect alimentary tract thus becomes the front line of insect counter-defense. It actively responds to dietary challenges by readjusting expression of its transcriptome and changing the repertoire of proteins in cells that line the digestive tract. Insect digestive enzymes, broadly classified into serine, cysteine, aspartate and metallo-proteases [1], play an important role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 44 publications
1
23
0
1
Order By: Relevance
“…Probes P6 to P8 resulted from annealing two complementary oligonucleotides. These oligonucleotides were first end-labeled separately with 0.73 M [␥-32 P]ATP using T4 DNA polynucleotide kinase, then mixed in complementary pairs as previously described (12). After annealing, the double-stranded oligonucleotide probes were purified with QIAquick Nucleotide Removal kit (Qiagen).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Probes P6 to P8 resulted from annealing two complementary oligonucleotides. These oligonucleotides were first end-labeled separately with 0.73 M [␥-32 P]ATP using T4 DNA polynucleotide kinase, then mixed in complementary pairs as previously described (12). After annealing, the double-stranded oligonucleotide probes were purified with QIAquick Nucleotide Removal kit (Qiagen).…”
Section: Methodsmentioning
confidence: 99%
“…We detected retarded bands of different mobility in control (scN-unadapted) and scN-fed (-adapted) insects, which implies that different binding proteins might be interacting with the CmCatB promoter in the two insect groups. In unchallenged control insects, we demonstrated that specific association of a COUP-element and CmSvp, a homolog of the COUP-interacting transcription factor (COUP-TF), resulted in repression of CmCatB (12). Its high abundance in unadapted insects and reduced expression in adapted insects supported the repressor function.…”
mentioning
confidence: 86%
See 3 more Smart Citations